2011
DOI: 10.3810/psm.2011.05.1893
|View full text |Cite
|
Sign up to set email alerts
|

A Carbohydrate-Restricted Diet during Resistance Training Promotes More Favorable Changes in Body Composition and Markers of Health in Obese Women with and without Insulin Resistance

Abstract: A carbohydrate-restricted diet promoted more favorable changes in weight loss, fat loss, and markers of health in obese women who initiated an exercise program compared with a diet higher in carbohydrate. Additionally, obese women who initiated training and dieting with higher HOMA levels experienced greater reductions in blood glucose following an HP diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 39 publications
(52 reference statements)
8
52
0
Order By: Relevance
“…Fat mass was reduced from 41.24 ± 6.74 to 34.99 ± 6.74, a fall of 15.1% (p < 0.0001). As in previous studies no significant differences were observed in total body water expressed as percent of body weight [22,27]. Waist circumference was reduced by an average of 9.46 cm from 106.56 ± 15.38 to 97.10 ± 12.69, a fall of 8.9% (p < 0.0001).…”
Section: Resultssupporting
confidence: 79%
“…Fat mass was reduced from 41.24 ± 6.74 to 34.99 ± 6.74, a fall of 15.1% (p < 0.0001). As in previous studies no significant differences were observed in total body water expressed as percent of body weight [22,27]. Waist circumference was reduced by an average of 9.46 cm from 106.56 ± 15.38 to 97.10 ± 12.69, a fall of 8.9% (p < 0.0001).…”
Section: Resultssupporting
confidence: 79%
“…The rationale has been that there are thermogenic advantages in metabolizing protein compared to carbohydrate and that a higher amount of protein in the diet can help maintain fat free mass during weight loss thereby helping minimize reductions in resting energy expenditure that is often associated with weight loss [14,16]. Our previous research examining the efficacy of the exercise and diet program used in this study provides some support to this theory [20,21,23]. Therefore, we hypothesized that women with knee OA may experience greater weight loss and therapeutic benefits from following a higher protein diet.…”
Section: Discussionmentioning
confidence: 73%
“…These employ a variety of strategies, including the use of MRs. Several commercial programs have been studied; research publications include those of both proponents and critics [17][18][19][20][21][22][23][24]. In general, the main criticisms of commercial weight-loss programs include cost [25], attrition rates [26], modest weight loss results, and overall suboptimal evidence to support their use [25].…”
Section: Introductionmentioning
confidence: 99%